Anatomical Considerations for Biliary Interventions: Navigating Challenging Cases - Wallace, Alex; Crawford, Daniel; Ozen, Merve; Patel, Indravadan (Seminars in Interventional Radiology, 2025)
A thorough understanding of normal biliary anatomy, common variants, and surgically altered anatomy is essential for the success of biliary interventions. Variations in biliary anatomy are seen in up to 40% of patients and frequently influence procedural planning and outcomes. This review highlights classical biliary anatomy, its common variations, and the challenges posed by surgical modifications, such as those encountered after cholecystectomy, liver resection, or biliary reconstructions. Case-based examples are used to explore the implications of these variations and modifications on interventional approaches, including the management of bile leaks, strictures, and complex obstructions. Strategies incorporating advanced imaging and procedural techniques, such as rendezvous interventions, are discussed to address complications and optimize outcomes. This article provides a practical framework for interventional radiologists to navigate challenging biliary cases with confidence and precision.
Keywords: biliary anatomy; biliary variants; bile stricture; rendezvous procedures; interventional radiology